Efektivitas Dapur Umum di Posko Tanggap Darurat Bencana (TDB) dalam Pemenuhan Kebutuhan Gizi pada Anak-Anak Pasca Bencana di Kelurahan Hutanabolon Kecamatan Tukka - Fridella Grace Natalia Tarigan; Rumiris Simatupang; Percaya Hia; Siti Ratna Harefa; Soeandi Malik Pratama (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Floods and landslides in Hutanabolon Village, Tukka District, Central Tapanuli Regency have disrupted access to food and health services, particularly for vulnerable groups such as children. Public kitchens, as the frontline of emergency nutrition response, face challenges in providing food that meets the specific nutritional needs of children. This study aims to evaluate the effectiveness of public kitchens at Disaster Emergency Response Posts (TDB) in meeting the nutritional needs of post-disaster children, identify supporting and inhibiting factors, and formulate recommendations for improving the public kitchen management system. The research employed a descriptive evaluative approach using survey methods, structured interviews, direct observation, 24-hour dietary recall, and anthropometric measurements (weight and height). The study subjects included 15 children aged 1–12 years and 8 public kitchen managers selected purposively. Data were analyzed descriptively by comparing nutritional intake against the Recommended Dietary Allowance (RDA) standards and analyzing kitchen management practices based on emergency nutrition guidelines. The findings revealed that children's average energy intake was only 1,140 kcal/day (below the minimum standard of 1,200–2,000 kcal/day) and protein intake was 18.7 g/day (below the standard of 20–35 g/day). A total of 33.3% of children were classified as having malnutrition to severe malnutrition based on weight-for-age indicators. Public kitchen management showed weaknesses in menu planning (100% had no child-specific menu), managers' nutritional knowledge (62.5% categorized as low), food availability (75% relied on instant aid without variation), and limited cross-sectoral coordination (50%). The effectiveness of public kitchens in meeting children's nutritional needs after disasters remains low.